2013
DOI: 10.1002/app.38909
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of shear stress at the tool‐part interface during autoclave processing of prepreg composites

Abstract: In this article, shear stress between an aluminum tool and a carbon fiber-epoxy prepreg is characterized during cure using polymeric release agent and release film at the tool-part interface. The effects of surface roughness, release materials, pull-out speed, temperature, and normal force (autoclave pressure) on the shear stress are investigated using a customized friction rig. Results show that the interfacial shear stress decreases as the temperature increases and it increases as the normal force increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Thus, researchers are focused on the development of Ni lay-up tools via electrochemical methods since Ni has a rather mediocre CTE and is reliable under harsh environmental conditions [14]. Additionally, other important concerns about the tooling material are the thermal cycle durability and wear resistance [15]. Several studies related with the experimental investigation of the tool/part interface were conducted to determine durability and perform life cycle assessment [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, researchers are focused on the development of Ni lay-up tools via electrochemical methods since Ni has a rather mediocre CTE and is reliable under harsh environmental conditions [14]. Additionally, other important concerns about the tooling material are the thermal cycle durability and wear resistance [15]. Several studies related with the experimental investigation of the tool/part interface were conducted to determine durability and perform life cycle assessment [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, other important concerns about the tooling material are the thermal cycle durability and wear resistance [15]. Several studies related with the experimental investigation of the tool/part interface were conducted to determine durability and perform life cycle assessment [15][16][17][18]. Corresponding studies showed that Ni electroplating with sulphamate solution reveals lower damage to human health than four wellknown different thermal spraying processes (wirearc, plasma, high velocity oxygen fuel (HVOF) and cold spray) which is of signifance for manufacturers of aerospace platforms.…”
Section: Introductionmentioning
confidence: 99%
“…Twigg et al 9,10 measured the interfacial shear stresses using strain gauges to analyze the tool-part shear interaction during composite processing. Joven et al 11 utilized a pull-out friction test rig to measure the shear stress between an aluminum tool and composites, and the different influence factors were studied. Ersoy et al 12 also employed a pull-out test device and the overlapping plies were pulled against each other at different rates in a servo-hydraulic testing machine.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the varying material properties, the tool-part interaction, moisture, fiber volume fraction gradients through thickness, composites compaction, and fiber wrinkle can also affect the residual stresses distortions. 8,2429 It should be noted here that process-induced distortions in the composite structures are highly dependent on the material system due to potentially significant difference on material straining behavior in different states. 30,31 Prior to selecting a suitable constitutive law, the accurate characterization of material straining behavior is of equal importance.…”
Section: Introductionmentioning
confidence: 99%